2015
DOI: 10.1016/j.jngse.2015.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in gas hydrate-based CO2 capture

Abstract: a b s t r a c tHydrate-based CO 2 capture (HBCC) has received increasing attention, due to such advantages as the mild operating pressure and temperature, the ease of regeneration and its unique separation mechanism. This review paper is focused on the chemical additives and the mechanical methods that have been investigated to improve the CO 2 separation efficiency and energy consumption through HBCC technology. Detailed comparisons of the effects of various chemical additives and mechanical methods on gas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(109 citation statements)
references
References 93 publications
1
108
0
Order By: Relevance
“…One advantage of semi-clathrates in storage purposes is that it allows for more guest molecules compared to promoters like THF, which do not alter the cage. Li et al [62] examined a hydrate-based CO2 separation process from a fuel gas mixture and observed that TBAB range of 0.14-1.00 mol% increased the induction time and hydrate growth rate while also increasing CO 2 storage capacity of the clathrate.…”
Section: Promotersmentioning
confidence: 99%
“…One advantage of semi-clathrates in storage purposes is that it allows for more guest molecules compared to promoters like THF, which do not alter the cage. Li et al [62] examined a hydrate-based CO2 separation process from a fuel gas mixture and observed that TBAB range of 0.14-1.00 mol% increased the induction time and hydrate growth rate while also increasing CO 2 storage capacity of the clathrate.…”
Section: Promotersmentioning
confidence: 99%
“…A self-contained storage vessel consisting of a low-temperature-grade carbon steel coded vessel and insulation and control systems equipped with approved class valves, piping, and fittings was considered. So far, CO2 separation and capture from waste gas by means of CO2 hydrate has been proposed [8][9][10]. Figure 7 shows the CO2 hydrate production system [11].…”
Section: Basic Principle Of Various Applied Separation and Recovery Dmentioning
confidence: 99%
“…The transportation cost in the case of a cylinder truck or a CO2 hydrate tank lorry was calculated with Equation (8) assuming that the cost per unit of transport volume was proportional to the transport distance.…”
Section: Calculating the Transportation Costmentioning
confidence: 99%
“…In recent years, the kinetic parameters of clathrate hydrate formation (such as induction time, the quantity of gas uptake and growth rate) in the presence of different additives have been studied by many researchers (Arjang et al 2013;Bi et al 2009;Dashti et al 2015;Farhang et al 2014;Fazlali et al 2013;Ganji et al 2007a, b;Kang and Lee 2010;Kumar et al 2013;Lirio et al 2013;Manteghian et al 2013;Mohammadi et al 2014a;Ricaurte et al 2014;Rogers et al 2007;Roosta et al 2015;Sabil et al 2010;Torré et al 2011;Zhang et al 2004Zhang et al , 2007. Mohammadi and coworkers studied the impact of sodium dodecyl sulfate and silver nanoparticles on the kinetic parameters of CO 2 clathrate hydrate formation (Mohammadi et al 2014a).…”
Section: Introductionmentioning
confidence: 99%